Building a Standout Personal Brand: Candidate Branding Strategies for Youth Unemployment (Gen Z) - Herlitah, H; Febriantina, Susan; Amniah, Hania; Kurnianti, Destria (Proceedings International Conference on Education Innovation and Social Science, 2025)
Advances in digital technology have transformed the global employment landscape, particularly for Generation Z, who have been raised in an era dominated by the internet and social media. This shift necessitates strategic preparation to compete effectively in the job market. This community engagement initiative aimed to strengthen the competencies of students from Universitas Negeri Jakarta and the University of Sabah Malaysia in developing impactful personal branding and candidate branding. Conducted in July 2025 in a hybrid format, the program engaged 70 participants through interactive lectures and Q&A sessions. Core topics included the principles of personal branding-authenticity, visibility, value, and digital presence as well as candidate branding strategies using social media, storytelling, and gamification. Pre- and post-test evaluations demonstrated notable improvements in participants' understanding of branding concepts and their application in recruitment contexts. The program contributes to preparing young professionals to be more adaptive, professional, and competitive in the global labor market.